Dorosły w świadomości przedszkolaka. Esej prawie naukowy - Alicja Jurgiel-Aleksander (Problemy Wczesnej Edukacji)
The aim of the following text is to present various manners of thinking about adults by five-year olds. On the basis of group interviews the author tries to recognize how children perceive adults. Despite the fact that this research ought to be treated only as a case study, the outcome shown in the essay depicts the children’s world. What is more it also shows how we, the adults, rear children. It was demonstrated that children view us as individuals physically resembling themselves, extremely busy at work, privileged when it comes to doing things that children cannot, great role models and good guardians. They do realize that in the adult world there are people who can do harm to them. To us it may seem that all these revelations are nothing new, but the results can show that we fail to treat children as partners.